A work of artificial generative intelligence as an object of copyright protection - Fominova, Kamilia Edita; Bugys, Rolandas (Vilnius University Open Series, 2024)
This coursework examines the relationship between the work of artificial generative intelligence and copyright and looks at the possibilities of copyright protection for such work. After evaluating and presenting the concepts of work and artificial intelligence, and after examining an AI work through the personality, labour and utilitarian theories, it is apparent that each case is different in terms of whether such a work could be subject to copyright protection. In the context of the personality and labour theories, an AI work cannot be the subject of copyright protection, whereas the latter, viewed through the prism of the utilitarian theory, is not only capable of being copyrightable, but also must be protected by the law. Looking at the question of authorship of this type of work on international level, the lack of uniform legal regulation is evident. However, it is clear from the recent views expressed by the European Parliament regulations and in the case-law of United States of America, that a work created using artificial generative intelligence as a tool is likely to be eligible for copyright protection, but that such a work will also be subject, amongst other requirements, to the usual criteria for assessing the individuality, or otherwise originality, of a personal intellectual creation.